2023
DOI: 10.1109/access.2023.3242616
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Multikey Cryptography Technique for Video Communication

Abstract: Online video streaming is becoming more widespread in people's everyday entertainment routines. Protecting copyright and piracy has become a key concern in real-time video streaming systems. This research provides a revolutionary multi-key and hybrid cryptography approach to offer security. This work describes the software implementation of video encryption and decryption employing continuous systems based on the Elliptic Curve Cryptography approach as pseudorandom encryption key generators. This approach crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…This study [107] introduces a unique approach for enhancing the security of video communication using multikey cryptography technology. This approach uses RSA and ECC algorithms to accomplish an asymmetric cryptographic methodology.…”
Section: Hybrid Cryptographymentioning
confidence: 99%
“…This study [107] introduces a unique approach for enhancing the security of video communication using multikey cryptography technology. This approach uses RSA and ECC algorithms to accomplish an asymmetric cryptographic methodology.…”
Section: Hybrid Cryptographymentioning
confidence: 99%
“…From this literature, it is observed that the hybrid model is a suitable method for enhancing the robustness of secured data. The previous work [13] concentrated on combining AES and ECC to achieve hybrid and multi-key encryption techniques. However, there is notable work on user-attribute-based key generation techniques.…”
Section: Related Workmentioning
confidence: 99%
“…A novel multi-equation-based multi-key crypto technique is proposed in this study. We have improved upon the method proposed in [13] using multi-equation and user attributes. The previous method uses RSA, AES, and ECC equations to encrypt video chunks.…”
Section: Proposed Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations